Antibiotic susceptibility and molecular epidemiology of Panton–Valentine leukocidin-positive meticillin-resistant Staphylococcus aureus: An international survey. Issue 1 (March 2014) - Macedo-Viñas, Marina; Conly, John; Francois, Patrice; Aschbacher, Richard; Blanc, Dominique S.; Coombs, Geoffrey; Daikos, George; Dhawan, Benu; Empel, Joanna; Etienne, Jerome; Figueiredo, Agnes Marie Sá; George Golding & CNISP,; et al.
Abstract: The antibiotic susceptibility and molecular epidemiology of Panton–Valentine leukocidin (PVL)-positive meticillin-resistant Staphylococcus aureus (MRSA) isolates reported from 17 countries in the Americas, Europe and, Australia-Asia were analysed. Among a total of 3236 non-duplicate isolates, the lowest susceptibility was observed to erythromycin in all regions. Susceptibility to ciprofloxacin showed large variation (25%, 75% and 84% in the Americas, Europe and Australia-Asia, respectively). Two vancomycin-intermediate PVL-positive MRSA isolates were reported, one from Hong Kong and the other from The Netherlands. Resistance to trimethoprim/sulfamethoxazole and linezolid was <1%. Among 1798 MRSA isolates from 13 countries that were tested for the requested 10 non-β-lactam antibiotics, 49.4% were multisusceptible. However, multiresistant isolates (resistant to at least three classes of non-β-lactam antibiotics) were reported from all regions. Sequence type 30 (ST30) was reported worldwide, whereas ST80 and ST93 were exclusive to Europe and Australia, respectively. USA300 and related clones (ST8) are progressively replacing the ST80 clone in several European countries. Eight major clusters were discriminated by multilocus variable-number tandem repeat assay (MLVA), showing a certain geographic specificity. PVL-positive MRSA isolates frequently remain multisusceptible to non-β-lactam agents, but multiresistance is already prevalent in all regions. Surveillance of MRSA susceptibility patterns should be monitored to provide clinicians with the most current information regarding changes in resistance patterns.